Programação linear inteira aplicada no planejamento da alocação de vagões de carga - Melo, Marcello Calado Vieira de (2008)
Load transportation attendance for demand is related tothe process of wagon allocation that in its turn, is associated with the way by which the decision is taken. The distribution of the wagons to the shipment terminals depends on the planning and movement of the empty wagons, being the trip of the empty wagon the parcel with bigger financial impact on the railroad system. In such a way, an efficient mechanism for wagon distribution is vital for the railroads, therefore providing important operational gains and cost savings. Thus, the purpose of this study is to analyze the problem related to the distribution of freight wagons and develop models in integer linear programming that will offer the analyst the opportunity to know in detail (in a tactical and operational level) the difficultiesfaced by the railroad, and to evaluate the setting of goals for retention times in rail yards, transit time, number of cars retained for maintenance, need to increase the fleet and even the profitability of the request or the feasibility for the implementation of the transport towards the operational assumptions in place.